Experimentos numéricos de um loop de gás úmido para estimativa da sobreleitura em placas de orifício: avaliação dos parâmetros governantes - Marochio, Elias Antonio Gomes Coelho (2016)
Flow measurement systems for differential pressure are widely industrial solutions, withthe orifice plate being the oldest element but still widely used. The accuracy of thesesystems is a fundamental requirement due to increasing demands of standards, regulationsand the requiriment to reduce production costs. In single-phase flow, the parameters forflow measurement are well-defined. However, in wet gas flow, the conditions are changeddue to the presence of a liquid phase in the gas flow, causing an overreading in thegas measurement. This paper proposes an evaluation of empirical correlations for gasflow correction, and an analysis of the influence parameters using the ComputationalFluid Dynamics (CFD). The evaluation of four correlations was performed using theexperimental data from Murdock (1962), and then compared with each other. The James(1965) correlation showed higher accuracy for the steam-water flow, and the Murdock (1962)correlation for air-water and natural gas-water, besides an evaluation of the operatingconditions of these correlations was performed. Furthermore, this paper also compared theinfluence parameters via the CFD to neglected by empirical correlations, being observedthat the parametersβ, Frl and the operating pressure influence overreading